Mountain bike magazine's complete guide to mountain biking skills expert tips on conquering curves, corners, dips, descents, hills, water hazards, and other all-terrain challenges (Rodale Press, 1996)
Guide to riding a mountain bike, with information on choosing the right bike, riding skills, how to ride in any weather, and tips from professional mountain bikers.